Use of liquid vinasse as a feed additive for Japanese quails - Martins, Poliana C.; de Oliveira, María C.; da Silva, Diones M.; Mesquita, Sabina A.; Oliveira, Higor C.; Marchesin, Wilson A. (Revista Colombiana de Ciencias Pecuarias, 2017)
Background: Liquid vinasse (LV) has probiotic properties and low pH. It is fed to animals as a solution to the disposal problem of this by-product. Objective: To evaluate the effects of increasing dietary levels of LV on growing performance, egg quality and economic viability for Japanese quails. Methods: One hundred sixty Japanese quails were included in a randomized study with five dietary treatments and four replicates per treatment. The treatments consisted of adding 0, 2.5, 5, 7.5, or 10% LV to a commercial quail feed for 84 d. Results: The LV inclusion resulted in a linear decrease in daily intake of dry matter (DM), crude protein (CP), gross energy, calcium, phosphorus, and in the feed conversion ratio. However, it resulted in a linear increase in egg-specific weight, eggshell weight, CP content in the DM, and a quadratic change in the ether extract content of the egg. The price per dozen eggs decreased linearly with the inclusion of LV. Conclusion: The best results were obtained by adding 10% LV, which made egg production more profitable.